Role of positron emission tomography in predicting early tumor response to neoadjuvant chemotherapy for breast cancer - N. G. Chanchikova; E. A. Karlova; A. S. Savelyeva; O. A. Silkina; V. I. Chernov; R. V. Zelchan; O. D. Bragina; A. A. Medvedeva (ABV-press, 2021)
Background. Neoadjuvant chemotherapy (NACT) is an important stage in the treatment of patients with breast cancer. Positron emission tomography/computed tomography (PET/СT) with fluorodeoxyglucose labeled with 18F (18F-FDG) is widely used as an effective method of metabolic tumor imaging at the stages of treatment. The aim of this study was to evaluate the possibility of using PET/CT with 18F-FDG to determine the early tumor response to NACT.Materials and methods. The results of PET/CT with 18F-FDG in 27 patients with breast cancer were retrospectively analyzed. The study was performed before the start of NACT, after the 2nd cycle of chemotherapy and after completion of all courses, the maximum accumulation of 18F-FDG in the tumor tissue (SUVmax), as well as the dynamics of changes in SUVmax after NACT (SUV(%)) were assessed. According to the results of postoperative morphological examination, the patients were divided into two groups: with complete tumor regression (pCR) and with no complete tumor regression (non-pCR).Results. The results of the study showed that the SUV(%) between the primary and interim examination, as well as between the intermediate and preoperative PET/CT scans, was 66.6 ± 13.3 % and 31.6 ± 17.5 %, respectively. The dynamics of SUV(%) between the primary and intermediate scans in the pCR and non-pCR groups was 79.04 ± 4.1 % and 63.8 ± 13.1 %, respectively (p = 0.02). The SUVmax value in the pCR and non-pCR groups during the primary PET/CT scan was 8.5 ± 0.78 and 8.2 ± 0.78, respectively (p = 0.5), while the intermediate scan was 1.8 ± 0.35 and 3.0 ± 0.14 (p = 0.03). Based on the research results, an ROC analysis was carried out, which showed that the optimal value of SUV(%) is 73.55 %, which showed the highest sensitivity and specificity.Discussion. Given that the change in SUVmax between primary and intermediate PET/CT was more pronounced than between intermediate and preoperative scans, it can be assumed that metabolic changes in the background of NACT are observed already in the early stages of treatment and persist until the end of therapy, thus, the ineffectiveness of the chemotherapy regimen can be determined using an intermediate PET/CT scan and a timely change in the treatment plan.Conclusions. We consider 73.55 % to be the optimal value of SUV(%) for intermediate PET/CT scanning; for this indicator and above, it is expected to expect a complete morphological response of the tumor to NACT. We believe that PET/CT with 18F-FDG at an intermediate stage of observation during NACT is a valuable method for predicting early tumor response to therapy.